Vendor Selection for Maintenance Using the Analytic Hierarchy Process (AHP) Method (Case study: PT. Global Sarana Mediakom) - Suci Elfitri; Anindya Agripina Hadyanawati (JTI: Jurnal Teknik Industri, 2025)
Objective vendor selection is crucial for a company as the right decision in choosing a vendor directly impacts service quality, operational cost efficiency, and business continuity. An unmeasured and subjective selection process can lead to risks such as decreased service quality, delays in task completion, and cost overruns, which can significantly harm the company. This study discusses a case study of vendor selection for maintenance at PT Global Sarana Mediakom using the Analytical Hierarchy Process (AHP) method. PT Global Sarana Mediakom is an information technology company specializing in data communication and internet services, with an operational network spanning more than 15 cities. This research focuses on addressing inefficiencies and subjectivity in the maintenance vendor selection process, which has traditionally relied on the lowest price or direct appointment without measurable evaluation. The AHP method is employed to evaluate and select the best vendor based on three main criteria: resource capability, completion time, and maintenance service cost. Data were collected through interviews and questionnaires with the company’s management. The data processing results indicate that Vendor A emerged as the best vendor with the highest priority score, followed by Vendor D, Vendor C, and Vendor B. The recommendations from this study include expanding the evaluation criteria and developing an AHP-based decision-support system to enable sustainable vendor management. Keywords: Analytical Hierarchy Process (AHP), Criteria, Multi-Criteria Decision Making (MCDM), Vendor Selection